2022
DOI: 10.24843//ejmunud.2022.v11.i02.p02
|View full text |Cite
|
Sign up to set email alerts
|

Peran Motivasi Kerja Dalam Memediasi Pengaruh Kompensasi Terhadap Kinerja Kayawan

Abstract: Kinerja karyawan merupakan hasil kerja yang dapat dicapai oleh karyawan berdasarkan kemampuan yang dimilikinya. Kinerja adalah hasil kerja nyata yang dicapai oleh karyawan dalam melaksanakan tugas yang diberikan kepadanya sesuai dengan kriteria dan tujuan yang ditetapkan oleh perusahaan. Tujuan dari penelitian ini adalah untuk menganalisis peran motivasi kerja dalam memediasi pengaruh kompensasi terhadap kinerja karyawan PT. BPR Gianyar Partasedana. Penelitian ini dilakukan di PT. BPR Gianyar Partasedana, juml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
2
0
1
5
Order By: Relevance
“…The findings of this study contrast with the conclusions drawn from the research conducted by (Candradewi & Dewi, 2019;Dewi & Ardana, 2022;Ulfah et al, 2020), which suggested that the impact of compensation on employee performance could be mediated by work motivation. Conversely, the current study's results align with the research conducted by Gerardine & Belinda (2018) and Priyanto (2016), highlighting that while compensation does have a positive influence, this effect on employee performance through work motivation is not deemed significant.…”
Section: Effect Of Motivation Mediates Competence On Employee Perform...contrasting
confidence: 99%
See 2 more Smart Citations
“…The findings of this study contrast with the conclusions drawn from the research conducted by (Candradewi & Dewi, 2019;Dewi & Ardana, 2022;Ulfah et al, 2020), which suggested that the impact of compensation on employee performance could be mediated by work motivation. Conversely, the current study's results align with the research conducted by Gerardine & Belinda (2018) and Priyanto (2016), highlighting that while compensation does have a positive influence, this effect on employee performance through work motivation is not deemed significant.…”
Section: Effect Of Motivation Mediates Competence On Employee Perform...contrasting
confidence: 99%
“…However, employees also expect their compensation to reflect the non-financial contributions they make, which is vital for their career development. These findings align with previous research conducted (Candradewi & Dewi, 2019;Dewi & Ardana, 2022;Parisuda & Mujiati, 2019), which indicated a favorable and substantial correlation between compensation and work motivation.…”
Section: Effect Of Compensation On Motivationsupporting
confidence: 91%
See 1 more Smart Citation
“…Sebaliknya, Bahri (2020) mengungkapkan motivasi kerja tidak memiliki peran mediasi terhadap hubungan kepemimpinan transformasional dengan kinerja karyawan Faktor lain yang mempengaruhi kinerja karyawan adalah kompensasi atau sesuatu yang diterima karyawan sebagai pengganti kontribusi jasanya kepada perusahaan. Guritno, dkk (2022), Dewi & Ardana (2022), Candradewi & Dewi (2019) mengungkapkan kompensasi berpengaruh positif terhadap motivasi kerja. Guritno, dkk (2022), Sinaga & Hidayat (2020), Efendi, dkk (2020) mengungkapkan kompensasi berpengaruh positif terhadap kinerja karyawan, sementara Magito (2020) dan Rezeki & Hidayat (2021).…”
unclassified
“…Guritno, dkk (2022), Sinaga & Hidayat (2020), Efendi, dkk (2020) mengungkapkan kompensasi berpengaruh positif terhadap kinerja karyawan, sementara Magito (2020) dan Rezeki & Hidayat (2021). Dewi & Ardana (2022), Efendi, dkk (2020), Candradewi & Dewi (2019) mengungkapkan motivasi kerja memediasi hubungan kompensasi dengan kinerja karyawan, sementara Guritno, dkk (2022) tidak.…”
unclassified